Cover page, CONTENTS (Discussion Papers, 2012)
"This special volume includes seven studies of the XIII. Polish-Hungarian Geographical Seminar. The topic of seminar was the comparison and analysis of socio-economical processes and finds the analogies and differences in the general regional and urban-rural transformation of Poland and Hungary. The majority of the lectures dealt with problems on the country level, but some study were based on regional investigation. This volume is published with the hope that it can promote a better understanding of the new aspects of regional transformation and the urban-rural relationship in Polish and Hungarian regions. With no doubt, the regions in former socialist countries are losers of the major economic and political transformation that the regime change brought about. Growing regional inequalities have hit these regions particularly hard. Especially rural regions do not seem to have any other choice than to follow the path that spanned approximately three decades in the West, from which emerged a dedicated network of viable policy frameworks, facilities and the institutional system needed for spatial development. Each stage of development will have to be covered. It is only time durations that could be shortened. For the time being, however, political commitment to this seems to be rather moderate."